Antitumor Potential of Extracellular Vesicles Released by Genetically Modified Murine Colon Carcinoma Cells With Overexpression of Interleukin-12 and shRNA for TGF-β1 - Rossowska, Joanna; Anger, Natalia; Wegierek, Katarzyna; Szczygieł, Agnieszka; Mierzejewska, Jagoda; Milczarek, Magdalena; Szermer-Olearnik, Bożena; Pajtasz-Piasecka, Elżbieta (Frontiers in Immunology, 2019)
Recent developments demonstrate that tumor-derived extracellular vesicles (EVs) could become a highly effective tool for delivery of antitumor factors. The main objective of the study was to determine whether EVs secreted by MC38 colon carcinoma cells genetically engineered for overproduction of interleukin (IL-)12 and/or shRNA targeting TGF-β1 are effectively loaded with these molecules and whether the obtained EVs could be an efficient tool for antitumor therapy. Fractions of EVs released by genetically modified MC38 cells [both modified tumor-derived exosomes (mTEx) and modified microvesicles (mTMv)] and those released by unmodified, wild-type MC38 cells were characterized in terms of loading efficacy, using real-time PCR and ELISA, as well as their antitumor potential. In order to examine the therapeutic potential of mTEx, they were applied in the form of sole treatment as well as in combination with dendritic cell (DC)-based vaccines stimulated with mTMv in the therapy of mice with subcutaneously growing MC38 tumors. The results demonstrated that genetic modification of wild-type MC38 tumor cells is an effective method of loading the molecules of interest into extracellular vesicles secreted by the cells (both TEx and TMv). The results also showed that mTEx secreted by cells engineered for overproduction of IL-12 and/or shRNA for TGF-β1 are able to induce tumor growth inhibition as opposed to TEx from unmodified MC38 cells. Additionally, antitumor therapy composed of mTEx (especially those deprived of TGF-β1) and DC-based vaccines allowed for regeneration of antitumor immunity and induction of the systemic Th1 response responsible for the sustained effect of the therapy. In conclusion, tumor-derived exosomes loaded with IL-12 and/or deprived of TGF-β1 could become an efficient adjuvant supporting induction of a specific antitumor response in both immuno- and chemotherapeutic schemes of treatment.